2013
DOI: 10.30955/gnj.000770
|View full text |Cite
|
Sign up to set email alerts
|

Removal of hexavalent chromium from electroplating wastewater by electrocoagulation with iron electrodes

Abstract: The performance of electrocoagulation using iron electrodes for the removal of hexavalent chromium from synthetic aqueous solutions and actual industrial electroplating wastewater was studied. Parameters affecting the electrocoagulation process, such as initial pH, applied current density, initial metal ion concentration, COD and time of electroprocessing were investigated. The optimum pH was found to be in the range 4-8. Initial chromium concentrations of 200 -800 mg L -1 did not influence its removal rate. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Electrocoagulation is a process consisting of creating metallic hydroxide flocs inside the wastewater by electro dissolution of soluble anodes. Dermentzis et al (2011) [133] found that some affecting parameters are pH, applied current density, and time, while initial Cr (VI) did not influence its removal rate by electrocoagulation. By contrast, Zewail et al (2014) [130] as well as Genawi et al (2020) [132] found that the initial chromium concentration determines the efficiency of the treatment.…”
Section: Electrocoagulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrocoagulation is a process consisting of creating metallic hydroxide flocs inside the wastewater by electro dissolution of soluble anodes. Dermentzis et al (2011) [133] found that some affecting parameters are pH, applied current density, and time, while initial Cr (VI) did not influence its removal rate by electrocoagulation. By contrast, Zewail et al (2014) [130] as well as Genawi et al (2020) [132] found that the initial chromium concentration determines the efficiency of the treatment.…”
Section: Electrocoagulationmentioning
confidence: 99%
“…The most used pairs of electrodes are made by Fe-Fe, Al-Al, or Al-Fe [129]. In the case of iron anodes, the Fe (II) ions reduce Cr (VI) to Cr (III) in alkaline to neutral medium, while they are oxidized to Fe (III) ions, according to the following reaction: CrO 4 2− + 3Fe 2+ + 4H 2 O + 4OH − → 3Fe(OH) 3 + Cr(OH) 3 [133]. Consequently, both the Fe (III) and Cr (III) combine with OH-ions, forming insoluble hydroxides which precipitate.…”
Section: Electrocoagulationmentioning
confidence: 99%